A participação da comunidade escolar na gestão da educação infantil de Betim/MG - Otavio Henrique Ferreira da Silva (2016)
This is study have as objective analyze the participation of the schoolingcommunity in the management of Early Childhood Education and discuss the means that relation this participantion has with the offer of a public service, free and of quality in the municipality of Betim located in Minas Gerais state. The methodology used was based on literature revision, documentary analyzis and field research through of interviews and discussion groups with families, professionals e community leaders of two public institutions of early childhood education of city. The colleted data were analyzed by the method content analysis and structured into two categories and seven subcategories. From this study, can consider that there is a great need of affectivity in the relation between the subjects of shooling community; in recent yars there have been a great reduction in the number of pedagogical and administrative meetings and collectiveschooling moments in institutions; where there are times for the participation of families they are seen by the different subjects as being less participative; about the management of the CIMs one of the great chellenges facing the directors is the management of outsourced professionals; the municipal government has not made possible the conditions to reach an integral democratic management of public education institutions with community participantion in decison-making;the pedagogical work developed in the institutions give great emphasis shooling and the Pedagogical Political Project is less discussed theme in the Early Childhood Education of municipal network of Betim. Because it´s a research of the program of Professional Master´s Educations and Teaching, two products were developed during this study: a um book about historical development of the policy of Early Childhood Education in the of Betim and training course on the implementation of Pedagogical Political Project in the Early childhood Education.